2018
DOI: 10.1111/1460-6984.12442
|View full text |Cite
|
Sign up to set email alerts
|

Association of proximal elements of social disadvantage with children's language development at 2 years: an analysis of data from the Children in Focus (CiF) sample from the ALSPAC birth cohort

Abstract: Background An association between social disadvantage and early language development is commonly reported in the literature, but less attention has been paid to the way that different aspects of social disadvantage affect both expressive and receptive language in the first 2 years of life. Aims To examine the contributions of gender, parental report of early language skills and proximal social variables (the amount of stimulation in the home, the resources available to the child and the attitudes/emotional sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 43 publications
8
42
0
Order By: Relevance
“…Significant, direct paths from early SES to all predictor variables and to the academic outcome measure were observed. This complements the findings of Law et al (2019), who reported similar SES effects on language development at age 2 years in the ALSPAC dataset; we now provide evidence of such effects extending into later childhood. The present results extend previous findings to demonstrate that early SES influences upon literacy outcomes remain even when a number of other factors are taken into consideration: social adjustment and literacy skills at age 5 years, and PIQ, decoding skills, and language development and social development aged 7-9 years and literacy outcomes aged 11 years.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Significant, direct paths from early SES to all predictor variables and to the academic outcome measure were observed. This complements the findings of Law et al (2019), who reported similar SES effects on language development at age 2 years in the ALSPAC dataset; we now provide evidence of such effects extending into later childhood. The present results extend previous findings to demonstrate that early SES influences upon literacy outcomes remain even when a number of other factors are taken into consideration: social adjustment and literacy skills at age 5 years, and PIQ, decoding skills, and language development and social development aged 7-9 years and literacy outcomes aged 11 years.…”
Section: Discussionsupporting
confidence: 89%
“…This adds to mounting evidence that quality of ELCE makes a difference even in otherwise adverse circumstances. To give some examples, mitigating effects of higher quality ELCE have been reported for early language development (Law et al, 2019), early cognitive development (Melhuish, 2010;Melhuish et al, 2008), and even on academic achievement at GCSE and A level (Sammons et al, 2018). Our findings are also congruent with research beyond the UK, including studies from Australia, Germany and USA.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations